TMA-93 for Diagnosing Amnestic Mild Cognitive Impairment: A Comparison With the Free and Cued Selective Reminding Test. Issue 5 (August 2019) - Rodrigo-Herrero, Silvia; Carnero-Pardo, Cristóbal; Méndez-Barrio, Carlota; De Miguel-Tristancho, Miguel; Graciani-Cantisán, Eugenia; Sánchez-Arjona, María Bernal; Maillet, Didier; Jiménez-Hernández, María Dolores; Franco-Macías, Emilio
Background: TMA-93 examines binding by images, an advantage for the less educated individuals. Aim: To compare the discriminative validity of TMA-93 against the picture version of Free and Cued Selective Reminding Test (FCSRT) to distinguish patients with amnestic mild cognitive impairment (aMCI) from normal controls (NCs) without excluding less educated individuals. Methods: Design: Phase I diagnostic evaluation study. Participants: A total of 30 patients with aMCI and 30 NCs matched for sociodemographics variables. Statistical Analysis: The diagnostic accuracy for each test was calculated by conducting receiver operating characteristic curve analysis. Hanley and McNeil method was used to compare diagnostic accuracy of different tests on the same sample. Results: Up to 41.7% of the sample had less than a first grade of education. Both tests showed excellent diagnostic accuracy. The comparisons did not show significant differences. Conclusions: TMA-93 is so accurate as FCSRT to differentiate aMCI from controls including less educated individuals. The test could be considered as a choice in this sociodemographic context.